Dreams, questions, struggles : South Asian women in Britain - Wilson, Amrit, 1941- (Pluto, 2006)
From schoolgirls to matriarchs, single mothers to extended families, and businesswomen to factory workers, the experience of Asian women in Britain today is polarised by class and religion. This book explores the lives and struggles of two generations of British Asian women to present a political account of their experiences: personal and public, individual and collective, their struggles take on power structures within the family, the community and, on occasion, the British state. Combining their personal testimony within a theoretical framework, Amrit Wilson locates their experiences in the wider context of global and regional politics. She examines the diverse issues that affect Asian women's lives, including: the impact of the feminist movement; domestic violence; marriage; representations of Asian women; and mental disturbance and suicide.